Fundamental Mechanisms of the Cell Death Caused by Nitrosative Stress - Wang, Fulin; Yuan, Qiuhuan; Chen, Fengying; Pang, Jiaojiao; Pan, Chang; Xu, Feng; Chen, Yuguo (Frontiers in Cell and Developmental Biology, 2021)
Nitrosative stress, as an important oxygen metabolism disorder, has been shown to be closely associated with cardiovascular diseases, such as myocardial ischemia/reperfusion injury, aortic aneurysm, heart failure, hypertension, and atherosclerosis. Nitrosative stress refers to the joint biochemical reactions of nitric oxide (NO) and superoxide (O2-) when an oxygen metabolism disorder occurs in the body. The peroxynitrite anion (ONOO-) produced during this process can nitrate several biomolecules, such as proteins, lipids, and DNA, to generate 3-nitrotyrosine (3-NT), which further induces cell death. Among these, protein tyrosine nitration and polyunsaturated fatty acid nitration are the most studied types to date. Accordingly, an in-depth study of the relationship between nitrosative stress and cell death has important practical significance for revealing the pathogenesis and strategies for prevention and treatment of various diseases, particularly cardiovascular diseases. Here, we review the latest research progress on the mechanisms of nitrosative stress-mediated cell death, primarily involving several regulated cell death processes, including apoptosis, autophagy, ferroptosis, pyroptosis, NETosis, and parthanatos, highlighting nitrosative stress as a unique mechanism in cardiovascular diseases.